Analysis of Healthcare Human Resources Capacity in the Management and Quality Assurance of Medical Record Data in the Digitalization Era - Weni Tri Purnani; Darmining; Miranty Andrian Deaningsi; Sasa Acnetia; Amanda Putri Anggraini (Research and Evidence on Knowledge in Administration and Management — Medical Electronic Data and Information Systems, 2025)
The success of Indonesia's digital health transformation critically relies on healthcare Human Resources (HR) capacity and robust Electronic Medical Records (EMR) quality assurance. This study performs an aggregate quantitative analysis using official national data (BPPSDMK, PORMIKI/PPNI) to correlate HR capacity with EMR quality indicators. Results reveal a significant HR imbalance, with 70% concentration in urban areas and a training gap (only 65% of professionals certified/trained). Regression analysis confirmed a strong positive statistical relationship (β=0.75, p<0.01), proving that HR capacity explains 56% (R2=0.56) of the variation in EMR quality. Furthermore, official reports indicate systemic failures in audit trail implementation, including limited access and system instability, compromising data integrity. The strong empirical evidence underscores that sustained, equitable investment in HR training and distribution is the most critical non-technical lever for quality improvement. Therefore, equitable HR development, mandatory standardized audit trail SOPs, and robust digital infrastructure are essential for ensuring high-quality and consistent digital medical record management nationwide.